Towards Healthy and Sustainable Diets Perspectives and Policy to Promote the Health of People and the Planet - Sarlio, Sirpa (SpringerBriefs in Public Health,, 2018)
This clear-sighted volume synthesizes wide-ranging knowledge of human food consumption, food production systems, and sustainability to offer methods of improving the impact of food choices on people and the environment. The comprehensive coverage addresses myriad challenges and paradoxes (e.g., health-conscious food choices that put greater stress on the planet, hunger amidst plenty) associated with the production of sustainable, nutritious food. Direct and complex links between local and global issues are highlighted in innovative approaches to transforming food production from the farm to the table and from the policy desk to the real world. Chapters identify, examine, and offer realistic recommendations for achieving critical goals, among them: Supporting healthy people and communities within planetary boundaries Reduction and prevention of food waste Combining health and sustainability on the plate "Serving sustainable and healthy food to consumers and decision makers": from commitment to action. Investing in healthier and more sustainable production. Ensuring a healthy sustainable diet is a goal of all public policies. Towards Healthy and Sustainable Diets is geared toward professionals and policymakers dealing with food, nutrition, and environmental topics seeking new perspectives on longstanding issues in these interrelated areas. It also makes a suitable reference for students studying and conducting research in these areas.